NEEDS AND PROBLEMS IN ENGLISH FOR HOSPITALITY INDUSTRIES: A CASE STUDY OF THE HOTEL EMPLOYEES AT MEOTEL HOTEL KEBUMEN - Hastri Firharmawan; Alek Andika (Journal of English Language Learning, 2019)
Hospitality industry is one of the important sectors to play roles in the economic and tourism growth in Kebumen. Therefore, keeping this industry to be competitive in the future seems to be urgent. Hotel owners need to improve the quality of human resources, mainly the English communication skills. This research describes and analyzes needs and problems of English for hospitality industry at Meotel Hotel Kebumen. It involved 20 experienced hotel employees at the research site as the participants. Questionnaires were used in the data collection. The data were analyzed by frequency, percentage, mean, and standard deviation. The findings proved that the skills needed from the most required to the least one are speaking, listening, reading, and writing. The three most dominant language uses are to give services, to give information, and to give help. Problems in using English encountered included guessing unknown words due to limited vocabulary, lacking of grammar knowledge, inability to follow the speed, and lacking of confidence. Key words: needs, English, skills, hospitality industry